Spectral Computed Tomography Angiography with a Gadolinium-based Contrast Agent: First Clinical Imaging Results in Cardiovascular Applications - Nadjiri, Jonathan; Pfeiffer, Daniela; Straeter, Alexandra S.; Noel, Peter B.; Fingerle, Alexander; Eckstein, Hans-Henning; Laugwitz, Karl-Ludwig; Rummeny, Ernst J.; Braren, Rickmer; Rasper, Michael (Journal of Thoracic Imaging, 2018)
Purpose: Computed tomography angiography (CTA) requires IV application of iodine-based contrast agents. There are several medical conditions in which application is not advisable or even feasible, especially for elective examinations. Novel techniques such as monoenergetic reconstructions from dual-energy computed tomographic (CT) data have been shown to increase radiation attenuation of gadolinium (Gd)-based contrast agents in a phantom model. Therefore, the purpose of the present investigation was to evaluate the technical feasibility and image quality of clinical spectral CTA with a Gd-based contrast agent. Materials and Methods: Eleven consecutive patients with common indications for thoracic CTA and contraindications for iodine-based contrast agents were examined using clinical routine doses (0.2 mmol/kg) of Gd-based contrast agent with spectral CT. Monoenergetic reconstructions of the spectral data set were computed. Results: We performed 11 Gd-enhanced CTAs: 9 aortic angiographies, 1 coronary angiography, and 1 angiography of the pulmonary arteries. Image quality of the monoenergetic reconstructions with 40 keV (monoE40) was considered diagnostic by 2 experienced radiologists in each patient; the conventional CT reconstructions did not reach diagnostic image quality. MonoE40 reconstruction resulted in a substantial, ∼2-fold increase of intravascular Gd attenuation compared with the conventional images (P<0.0001). No relevant change of attenuation was observed for the myocardium or the skeletal muscle. Conclusions: With spectral CT and reconstruction of monoenergetic images with extrapolated 40 keV, Gd-based contrast agent thoracic angiography with clinical doses of Gd is technically feasible. Gd-based CTA seems a valuable alternative in patients with contraindications for iodine-based contrast media.
CRIS-Team Scopus Importer:2023-03-08
Keywords: dual energy; gadolinium; monoenergetic reconstruction; spectral computed tomography angiography